Identifying the impact of key parameters on the drying kinetics of onion (Allium cepa L.) slices - P. Kiran Kumar; Konijeti Ramakrishna; Sai Akshara Vemuri; Sireesha Koneru; Bandhavi Challa; Atul Singla; Nitin Duklan; Haider Alabdeli (Cogent Engineering)
This study investigates the drying kinetics of onion (Allium cepa L.) slices, analyzing the influence of four crucial drying parameters: temperature, velocity, humidity of the air and thickness of the product on hot air drying. Employing a comprehensive analysis, the goal is to pinpoint the most influential factor among these parameters that significantly affect the drying process. The experimental approach involves close monitoring of drying kinetics while varying drying conditions; The Taguchi Technique, utilizing an L16 orthogonal array, optimized onion slice drying with fewer experimental runs. Analysis of variation (ANOVA) quantified each parameter’s influence on drying, enhancing process efficiency. The findings illustrate that the temperature parameter exerts the most substantial influence on onion slice drying, contributing to 78.13% of drying time reduction and 51.33% in moisture ratio variation. The initial moisture content of the onion slices was measured at 85.7 to 88.0% (wet basis), with the final moisture content reaching 7% (wet basis). This research provides crucial insights for optimizing onion drying processes across diverse applications, including food preservation and production.